1999
DOI: 10.1007/s002280050594
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of clevidipine in healthy volunteers after intravenous infusion

Abstract: Clevidipine is a high clearance drug, which is rapidly metabolized to the corresponding inactive acid. The tmax value of the primary metabolite, and a virtually identical value of the initial half-life and the half-life for elimination from the central compartment, indicate that the initial rapid decline of the post-infusion blood levels is mainly due to elimination rather than distribution. The duration of action of clevidipine is short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…This metabolite is subsequently metabolized to a large extent by glucuronidation, oxidation or decarboxylation before excretion. The pharmacokinetics of the main metabolite, with a terminal half-life of approximately 9 h, differs markedly from clevidipine (15,16 administration of tritium-labeled clevidipine suggests biliary elimination and /or intestinal secretion of clevidipine and/or its metabolites (15).…”
Section: Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…This metabolite is subsequently metabolized to a large extent by glucuronidation, oxidation or decarboxylation before excretion. The pharmacokinetics of the main metabolite, with a terminal half-life of approximately 9 h, differs markedly from clevidipine (15,16 administration of tritium-labeled clevidipine suggests biliary elimination and /or intestinal secretion of clevidipine and/or its metabolites (15).…”
Section: Metabolismmentioning
confidence: 98%
“…However, characterizing pharmacokinetics of a drug with disposition models containing two or three exponential phases with different half-lives is sometimes done by arbitrary judgments. The important phases in describing the pharmacokinetic properties of clevidipine are those immediately after cessation of the infusion, since the initial rapid post-infusion decline in clevidipine levels is primarily related to elimination (15). Thus, use of decremental times rather than different half-lives is more appropriate for describing the pharmacokinetics of clevidipine.…”
Section: Half-life and Decrement Timesmentioning
confidence: 99%
“…The ideal perioperative antihypertensive agent would have rapid onset and short duration of activity with easy titration to effect and a low risk of overshoot hypotension [42]. The benefits and limitations of currently used agents are summarized in tables 3 and 4[29,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75]. Where available, comparison studies have been included; however, it should be noted that rigorous studies involving commonly used antihypertensives are few and far between and, with the exception of the ECLIPSE program, were completed more than a decade ago.…”
Section: Traditional Therapies For Perioperative Hypertension: Meritsmentioning
confidence: 99%
“…In two pharmacodynamic evaluations in healthy volunteers, clevidipine resulted in increases in heart rate by approximately 40% (from 59 to 82 bpm and from 53 to 75 bpm). 19,21 In both studies, heart rate returned to baseline values within 10 to 15 minutes after discontinuation of the infusion. 19,21 In ESCAPE-1, patients in both the clevidipine and placebo groups experienced increases in heart rate from a baseline of 71 and 76 bpm respectively to a maximum heart rate of 84 bpm in both groups.…”
Section: Adverse Effectsmentioning
confidence: 95%
“…Initial pharmacokinetic studies showed a mean blood clearance of 0.14 L/min/kg and a volume of distribution at steady state of 0.6 L/kg. 19 Clevidipine is highly protein-bound in humans (∼99.7%).…”
Section: Pharmacokinetic and Metabolism Profile Of Clevidipinementioning
confidence: 99%